Evaluation of Maize Cultivars for their Suitability under Organic Production System in North Eastern Hill Region of India - Layek, Jayanta; GI, Ramkrushna; Suting, Dauni; Ngangom, B.; R, Krishnappa; De, Utpal; Das, Anup (Indian Journal of Hill Farming, 2017)
The hill ecosystem of North Eastern region (NER) of India is suitable for organic farming due to very less use of fertilizer and agrochemicals, abundance of organic manure and favourable soil and climatic conditions. Maize is the most potential and predominant rainy season crop in the upland ecosystem of NER. A field experiment was carried out during kharif seasons of 2013 and 2014 to identify suitable maize cultivars having short duration and high yield potential under organic production system. Eleven varieties/ lines of maize comprising eight composites, one hybrid and two local lines were evaluated. Significantly, the highest chlorophyll index at 60 days after sowing (DAS) was recorded in the variety DA 61A followed by RCM 1-3 in both the years of experimentation. Cob weight was maximum in variety DA 61 A (221.8 and 223.8 g/cob in year 2013 and 2014, respectively). The highest grain yield was recorded in variety DA 61 A (3.33 t/ha and 3.39 t/ha in year 2013 and 2014, respectively) followed by RCM- 76 (3.26 t/ha and 3.29 t/ha). The highest soil organic carbon (SOC) was recorded under variety DA 61 A and RCM-75 (2.11 %) followed by RCM-1-3 and RCM 76 (2.10 %). For green cob production, RCM-75 and RCM-76 (75-80 days) recorded the shortest crop duration followed by DA 61A (80 days) and RCM 1-2 (85 days). However, for seed production, DA 61A took 110 days duration followed by RCM 1-2 (115 days). Local lines took 125-130 days for seed production. Cultivar DA 61 A registered the least Turcicum leaf blight severity with moderate severity for Maydis leaf blight and rust than other varieties. Thus, it can be concluded that DA 61A and RCM-76 cultivars of maize are most suitable for growing in hill conditions of NER under organic production system.